PENGARUH MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN TEKSTIL DI SMK SYAFI’I AKROM PEKALONGAN - Safitri, Emilia (Fashion and Fashion Education Journal, 2012)
Abstract The results of SMAN Syafi'i Akrom Pekalongan obtained data that the learning of textile subjects is still low, seen from the results of learning that still many not meet the standards of KKM. One of the learning models that can be used in textile learning is the Numbered Heads Together (NHT) model. The purpose of this research is to know and use various models of NHT learning on student learning outcomes in the subjects of Textile Lesson. The population in this research is the students of Fashion Class class X SMK Syafi'i Akrom Pekalongan communicating 16 students. The sample in this study using total sampling. Methods of data collection using test methods and nontes. Testing hypothesis 1 using Uji-t obtained thitung> ttable that is 4,98> 2,13. Testing of hypothesis 2 using N-Gain calculation obtained significance 0,33. Based on the results of research can be concluded that there is integration and 33% use of NHT learning model on student learning outcomes in the eyes of Textile Lessons. Keywords : Cooperative Learning, Numbered Heads Together (NHT), learning outcomes